QUANTITATIVE HISTOLOGICAL STUDY OF THE IMMUNE RESPONSE FOR OVARIAN CANCER AND ITS PROGNOSTIC SIGNIFICANCE - L. V. Khalikova (Креативная хирургия и онкология, 2017)
Studied the prognostic significance of factors such as the parameters of immune responses available evaluation underlight microscopy , without costly immunohistochemical and molecular genetic methods . Identified three characteristics that predicted the outcome of ovarian cancer - the average number of lymphocytes in the field of viewof the microscope x200 on the border of the tumor / metastasis , presence or absence of the same continuity and plasmacytoid lymphocytic shaft . Developed a regression equation to predict the course of ovarian cancer , which should contribute to improved health outcomes.